Identifikasi Faktor Transmigran Bertahan Tinggal Di Desa Hegar Manah Kecamatan Bintang Ara Kabupaten Tabalong - Bahrudin Bahrudin; Karunia Puji Hastuti; Parida Angriani (JPG (Jurnal Pendidikan Geografi), 2021)
The population problem in Indonesia is the rate of population growth and the imbalance in its distribution.  The transmigration program aims to balance the distribution of the population by regulating and directing people who have a high density to move to areas that are still sparsely populated, with the hope that development and population distribution can be evenly distributed. Hegar Manah Village.  Hegar Manah Village is a village located in Bintang Ara District, Tabalong Regency, which was one of the transmigrant placement villages in 1993. In 1993 transmigrants came to Hegar Manah Village as many as 300 families (KK), consisting of 150 families from the other side (Java Island) and 150 local transmigrant families (Kalimantan), in 2020 there are only 30 transmigrant families left. This study aims to analyze the factors that cause transmigrants to persist in living in Hegar Manah Village, Bintang Ara District, Tabalong Regency, by examining 4 factors that are considered influential on the reasons for transmigrants to survive, namely by examining the transmigrant economic sector, public infrastructure facilities, land/land ownership and social cultural or adaptation of transmigrants to the local physical and social environment.  This study uses a quantitative method with a descriptive approach.  Data collection was carried out by distributing questionnaires/questionnaires to 27 families of indigenous transmigrant communities who still survived.  Data analysis used descriptive statistics by calculating the percentage of each answer from respondents, and factor analysis by calculating the results of respondents' answers. The results showed that the transmigrant community persisted in living in Hegar Manah Village, Bintang Ara District because 1) they had sufficient land for the reason to survive.  2) good social culture or tolerance for very high differences, so as to create social and cultural harmony without discriminating against ethnicity, race, or religion.  3) economic or welfare factors are not the reason for transmigrants to stay.  4) the factor of infrastructure is not the reason for transmigrants to stay.Keywords: Transmigrant, survival factors